2011
DOI: 10.1016/j.ejso.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between morbidity after axillary surgery and long-term quality of life in breast cancer patients: The role of anxiety

Abstract: . The relationship between morbidity after axillary surgery and long-term quality of life in breast cancer patients: The role of anxiety. EJSO -European Journal of Surgical Oncology, WB Saunders, 2011, 37 (4) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
3
26
0
2
Order By: Relevance
“…These physical side-effects of treatment have a negative impact on patients' mental health and Quality of Life (QoL). For instance, patients who experience restrictions in ROM report poorer social and psychological well-being compared with patients without restrictions in shoulder ROM (Aerts, de Vries, Van der Steeg, & Roukema, 2011). Furthermore, pain reduces patients' sleeping quality and overall QoL, whereas painrelated disability regarding self-care and sexuality is an important predictor of mental health (Hack et al, 1999;Tasmuth, von Smitten, & Kalso, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These physical side-effects of treatment have a negative impact on patients' mental health and Quality of Life (QoL). For instance, patients who experience restrictions in ROM report poorer social and psychological well-being compared with patients without restrictions in shoulder ROM (Aerts, de Vries, Van der Steeg, & Roukema, 2011). Furthermore, pain reduces patients' sleeping quality and overall QoL, whereas painrelated disability regarding self-care and sexuality is an important predictor of mental health (Hack et al, 1999;Tasmuth, von Smitten, & Kalso, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…First, most studies that investigated anxiety in breast cancer survivors imparted knowledge/findings that can be generalized to several specific racial/ethnic groups (Aerts, De Vries, Van der Steeg, & Roukema, 2011;Cheung, Lee, & Chan, 2013), but not to African American women breast cancer survivors, indicating the paucity of research on this particular area. Additionally, there was a substantial literature on the many facets of TNBC among African women, which is well needed; however, there is a strong need to expand and build on the biobehavioral factors (for TNBC) among African American survivors, which is currently absent from the literature.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…It is plausible to surmise from this data that a woman could have adequate upper quarter range of motion and strength, but may avoid activities because of fear, pain, or emotional distress. Fear of lymphedema is an important behavior to address, as other authors have reported this as inhibiting function as well [18,31,45,46].…”
Section: Upper Extremity Activities Of Daily Livingmentioning
confidence: 94%
“…Other treatment-related factors including fatigue, pain, loss of upper extremity range of motion and strength, anxiety, changes in weight, unemployment, and neuropathy have also been suggested to compromise function and QOL [8,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%